Radiographers' opinions on radiography research in Norway – A national survey. Issue 2 (May 2017) - Vikestad, K.G.; Hafskjold, L.; Kjelle, E.; Sebuødegård, S.; Hofvind, S.
Abstract: Objective: The objective of the Norwegian Radiography Research Group is to establish a strategy for radiography research in Norway. A survey investigating radiographers' opinions on research was conducted to establish a basis for this strategy. Methods: A questionnaire was sent to all members of the Norwegian Society of Radiographers using the society's e-mail list from May 2014 (n = 2273). The respondents, 31% (n = 697), were divided into six groups; general radiographers (n = 392), specialised radiographers (n = 124), managers (n = 74), radiation therapists (n = 59), professors (n = 13), and others (n = 35). The questionnaire included four parts: introduction, participation in research, research performed at the respondent's work place, and opinions on radiography research. The first parts consisted of close-ended questions, while the fourth part also included a Likert scale. Results: Among all respondents, 63% respondents agreed that there is a need for radiography research and 50% agreed that general radiographers/radiation therapists should be the principal investigators of such research. However, only 19% reported participation in a research project during the last five years, and of those, 50% knew how the results of their research had been communicated. Conclusion: The majority of radiographers agreed that there was a need for radiography research and that radiographers/radiation therapists should take a leading role in such work. The results indicate that radiographers/radiation therapists would benefit from training in informal and formal research skills. Highlights: Two in ten radiographers took part in research activity in Norway. Six in ten agreed that there is a need for radiographic related research in Norway. Evidence-based practice, informal and formal research training represent the main aim to reach in the first strategy for radiography research in Norway.